Linguocultural peculiarities of paralinguistic elements in English and Uzbek languages - Qodirova , Navruza (The Lingua Spectrum, 2025)
This article investigates the linguocultural characteristics of paralinguistic elements in ceremonial contexts in English and Uzbek languages. It emphasizes non-verbal means of communication such as gestures, facial expressions, posture, and symbolic movements, which accompany and enhance spoken language during formal events. These elements serve as cultural markers that express respect, social roles, emotions, and ritual intentions. The study is based on comparative analysis of various ceremonies including weddings, official receptions, and religious events. It identifies both common and contrasting uses of paralinguistic elements in the two linguistic-cultural contexts. Attention is given to the cultural interpretations and communicative roles of these non-verbal signals, demonstrating how they align with verbal discourse to construct meaning. The findings highlight the importance of understanding paralinguistic features for accurate cross-cultural communication and translation. The study contributes to research in intercultural pragmatics, linguistics, and non-verbal communication by revealing the deep connection between culture, language, and ceremonial practice.